Divergent expectations : case studies of community-based tourism on the island of the gods, Bali : a thesis presented in partial fulfilment of the requirements for the degree of Master of International Development at Massey University, Palmerston North, New Zealand - Martokusumo, Kathlia Sari (Massey University, 2015)
This thesis examines the success of community-based tourism in Bali, a popular mass tourism destination in Indonesia. Presented as an unalloyed good and the antithesis of ‘bad’ mass tourism, community-based tourism is expected to create broad equitable distribution of benefits, expand livelihood options, empower local communities, and conserve both culture and the environment. In practice, however, it is difficult to find successful examples of community-based tourism. Most projects have failed to produce significant benefits and are too dependent on external assistance. Using four Balinese villages as case study sites, the views of the local community and support organisations were explored to find out what they perceive as successful community-based tourism. The results indicate that while there are many benefits enjoyed by the communities, most residents see that the community-based tourism initiative in their village is not yet successful. A key finding of the research is that while the communities recognise the socio-political, environmental and cultural benefits of the initiative in their village, they would like to enjoy more significant economic benefits, both at the community and individual household level. The thesis concludes that there are divergent expectations at play among the communities and the organisations supporting them as there is a difference in the emphasis of what success means between the community and the support organisations.
Keywords: Tourism; Community development; Social conditions; Indonesia; Bali Island; Research Subject Categories::SOCIAL SCIENCES::Social sciences